The Penned Parrot in the Writers’ Room: Four Stage Story Generation in Collaborative Screenwriting with AI (International Journal on Stereo & Immersive Media, 2025)
This artistic research article explores the application of Artificial Intelligence (AI) in the process of screenwriting, focusing on the Four Stage Story Generation method in collaborative screenwriting scenarios. The primary objective of this study is to explore and analyze the dynamics between human creativity and AI capabilities in crafting screenplays. By integrating AI into the traditional screenwriting process—which involves stages of writing, feedback, and rewriting—we investigate the transformative impacts on both the process and the outcomes of screenplay development.Our research employs GPT-4 to co-create a screenplay for a short film. This collaborative approach highlights the potential of AI to act as a creative partner, contributing to the ideation and development phases of the script. The study is structured around a four-stage model: thematic conception, story world conception, character conception, and dramaturgical conception. Each stage is designed to leverage the strengths of AI in generating content that adheres to established screenwriting paradigms while also pushing the boundaries of traditional creative processes.The findings from this study reveal that while AI can significantly enhance the screenwriting process by generating innovative ideas and content, it also presents challenges such as maintaining narrative coherence and depth in character development. The interaction between human screenwriters and AI showcases a complex interplay of creativity where AI’s contributions are curated and refined by human oversight. This research contributes to the understanding of AI’s role in creative industries and sets the stage for further explorations into the capabilities and limitations of AI in artistic collaborations.Keywords: Collaborative Screenwriting, Human-Machine-Interaction, GPT-4, prompting, Artistic Research